Monarchical Rule in Swaziland: Power is Absolute but Patronage is (for) Relative(s). (June 2017) - Woods, Dwayne
This article adopts a non-formalized decision−theoretic model to examine patronage strategies by the monarchy in Swaziland as a means to stave off threats to its hold on power. The article's main argument is that the logic of patronage is largely about controlling and monitoring local chiefs and placating royal princes with administrative positions and sources of revenue and limiting the insurrectionary potential of non-traditionalist urban groups to absolute monarchical power in Swaziland.